Shaping digital delight: The role of user experience in marketing - Abdeldjebar, Afif; Nadjat, Hadjab; Essaad, Serai Oum; Keltoum, Bentameur (The International tax journal, 2026)
In today’s hyper-connected world, where digital touchpoints define brand perception, user experience (UX) has evolved from a design concern to a strategic marketing imperative. This study explores the intersection of UX and marketing, highlighting how an intuitive, engaging, and emotionally resonant digital experience can drive brand loyalty, conversion rates, and long-term customer value. The study collected data from multiple touchpoints, such as websites and social media platforms, and employs regression analysis and correlation coefficients to evaluate how user experience dimensions influence marketing outcomes. This study concluded the pivotal role of user experience in driving marketing effectiveness for Apple Vision Pro. Future research could explore the integration of AI and AR to enhance personalized user experiences, investigate the long-term effects of emotional design on engagement and loyalty.